2016
DOI: 10.1080/09593330.2016.1240715
|View full text |Cite
|
Sign up to set email alerts
|

Energetic potential of algal biomass from high-rate algal ponds for the production of solid biofuels

Abstract: In this investigation, chemical characteristics, higher, lower and net heating value, bulk and energy density, and thermogravimetric analysis were applied to study the thermal characteristics of three algal biomasses. These biomasses, grown as by-products of wastewater treatment in high-rate algal ponds (HRAPs), were: (i) biomass produced in domestic effluent and collected directly from an HRAP (PO); (ii) biomass produced in domestic effluent in a mixed pond-panel system and collected from the panels (PA); and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The general fuel quality and specifications for solid biofuels of raw and processed materials are also evaluated through ISO 17225-2 standard (Alakangas 2014). (Mani et al 2004;Erlich et al 2005;Kaliyan and Morey 2009;Kargbo et al 2010;Serrano et al 2011;Brosse et al 2012;Cardoso et al 2013;Ivanova et al 2014;Bhagwanrao and Singaravelu 2014;Lizotte et al 2015) The bulk density also governs the energy density in solid biofuels, as the bulk density and lower heating value determine the energy density of biomass (Costa et al 2017), and a high bulk density in any form of solid biofuel (i.e., pellet or briquettes) denotes a higher energy density. Table 3 summarizes bulk density, heating value, ash content, and mechanical durability of selected biomass types.…”
Section: Bulk Densitymentioning
confidence: 99%
“…The general fuel quality and specifications for solid biofuels of raw and processed materials are also evaluated through ISO 17225-2 standard (Alakangas 2014). (Mani et al 2004;Erlich et al 2005;Kaliyan and Morey 2009;Kargbo et al 2010;Serrano et al 2011;Brosse et al 2012;Cardoso et al 2013;Ivanova et al 2014;Bhagwanrao and Singaravelu 2014;Lizotte et al 2015) The bulk density also governs the energy density in solid biofuels, as the bulk density and lower heating value determine the energy density of biomass (Costa et al 2017), and a high bulk density in any form of solid biofuel (i.e., pellet or briquettes) denotes a higher energy density. Table 3 summarizes bulk density, heating value, ash content, and mechanical durability of selected biomass types.…”
Section: Bulk Densitymentioning
confidence: 99%
“…However, the performance of the MBC is governed by culture time that affects the growth of algae (Qi et al, 2021; Valigore et al, 2012). Consequently, the effect on wastewater treatment, especially nutrient removal, needs to be optimized to meet the increasingly stringent wastewater treatment standards of MBC (Costa et al, 2017). Researches, at present, have shown that the wastewater treatment processed by MBC within hydraulic retention time (HRT) 2–7 days, increasing the time cost.…”
Section: Introductionmentioning
confidence: 99%